Empowering Communities by Sustainably Utilizing Tourism Waste Through Maggot-Based Feed Innovation for Biofloc Farming - Mufidah, Mufidah; Zahari, Muhammad; Hasminidiarty, Hasminidiarty (Jurnal Karya Abdi Masyarakat, 2024)
This community engagement program was conducted to address organic waste accumulation in the Gentala Arasy tourism area of Jambi City, which contributes to environmental pollution and affects public health. In collaboration with Bank Sampah Omah Sinau, the initiative focused on converting sugarcane pulp and corn cobs into fish feed for local biofloc-based catfish farming. The program adopted a participatory model consisting of awareness campaigns for local vendors, technical training in waste processing, modification of waste shredders to electric motor systems, cultivation of black soldier fly (BSF) larvae, and the production of pellet feed using organic waste materials. The modified equipment significantly reduced noise and air pollution while improving processing efficiency. Community members were actively involved in all stages, with evaluation results indicating that 70% of participants had developed the skills to independently produce pellet feed. The program also included workshops on financial literacy and small-scale business planning to support long-term sustainability. Despite challenges such as inconsistent waste supply and the absence of a structured distribution system, the initiative successfully enhanced the community’s capacity in sustainable aquaculture practices. This model highlights the potential of integrating appropriate technology and waste management for community empowerment and circular economic development.